Large‐Area 2D Layered MoTe2 by Physical Vapor Deposition and Solid‐Phase Crystallization in a Tellurium‐Free Atmosphere - Huang, Jyun‐Hong; Deng, Kuang‐Ying; Liu, Pang‐Shiuan; Wu, Chien‐Ting; Chou, Cheng‐Tung; Chang, Wen‐Hao; Lee, Yao‐Jen; Hou, Tuo‐Hung (Advanced materials interfaces, 2017)
Molybdenum ditelluride (MoTe2) has attracted considerable interest for nanoelectronic, optoelectronic, spintronic, and valleytronic applications because of its modest band gap, high field‐effect mobility, large spin–orbit‐coupling splitting, and tunable 1T′/2H phases. However, synthesizing large‐area, high‐quality MoTe2 remains challenging. The complicated design of gas‐phase reactant transport and reaction for chemical vapor deposition or tellurization is nontrivial because of the weak bonding energy between Mo and Te. This study reports a new method for depositing MoTe2 that entails using physical vapor deposition followed by a postannealing process in a Te‐free atmosphere. Both Mo and Te are physically deposited onto the substrate by sputtering a MoTe2 target. A composite SiO2 capping layer is designed to prevent Te sublimation during the postannealing process. The postannealing process facilitates 1T′‐to‐2H phase transition and solid‐phase crystallization, leading to the formation of high‐crystallinity few‐layer 2H‐MoTe2 with a field‐effect mobility of ≈10 cm2 V−1 s−1, the highest among all nonexfoliated 2H‐MoTe2 currently reported. Furthermore, 2H‐MoS2 and Td‐WTe2 can be deposited using similar methods. Requiring no transfer or chemical reaction of metal and chalcogen reactants in the gas phase, the proposed method is potentially a general yet simple approach for depositing a wide variety of large‐area, high‐quality, 2D layered structures. Physical vapor deposition followed by a postannealing process in a Te‐free atmosphere is developed to deposit high‐crystallinity 2H‐molybdenum ditelluride with a high field‐effect mobility. The proposed method is potentially a general yet simple approach for depositing a wide variety of large‐area, high‐quality, 2D layered structures.